DETERMINAN TATA KELOLA SYARIAH PADA BAITUL MAAL WAT TAMWIL (BMT) DI KOTA DEPOK - Ahmad Naufal Sarin; Ahmad Baehaqi (Jurnal Riset Keuangan dan Akuntansi, 2022)
Sharia governance is a governance concept unique to Islamic financial institutions. This study aims to investigate the effect of organizational culture, organizational commitment, internal control, and education on sharia governance in Baitul Maal wat Tamwil (BMT). The respondents of this study were the staff of grade-A BMT in Depok City with a sample that was determined randomly. Data were collected through surveys and analyzed using the structural equation modeling (SEM) method using SmartPLS. The results of this study indicate that organizational culture, internal control, and education have a significant positive effect on sharia governance. On the other hand, organizational commitment does not have a significant positive effect on sharia governance. These results encourage Islamic cooperatives to maintain the organizational culture, internal control, and education of management. On the other hand, BMT must strengthen the organizational commitment of management, even though their tenure is not long, because strong organizational commitment can improve sharia governance.Keywords: Shariah governance, Organizational culture, Internal control, Organizational commitment, Education, and Batul Maal wat Tamwil (BMT)